Evidence gap map of performance measurement and management in primary healthcare systems in low-income and middle-income countries. (16th August 2019) - Munar, Wolfgang; Snilstveit, Birte; Aranda, Ligia Esther; Biswas, Nilakshi; Baffour, Theresa; Stevenson, Jenniffer
Abstract : Introduction: We mapped available evidence on performance measurement and management (PMM) strategies in primary healthcare (PHC) systems of low-income and middle-income countries (LMICs). Widely used, their effectiveness remains inconclusive. This evidence gap map characterises existing research and evidence gaps. Methods: Systematic mapping of performance measurement and management research in LMICs from 2000 to mid-2018; literature searches of seven academic databases and institutional repositories of impact evaluations and systematic reviews. Using a combination of manual screening and machine learning, four reviewers appraised 38 088 titles and abstracts, and extracted metadata from 137 impact evaluations and 18 systematic reviews that met the inclusion criteria. The resulting visual representation of the evidence base was uploaded to a web-based platform. Results: Since 2000, the number of studies has increased; the first systematic reviews were completed in 2010. Two-thirds of the studies were conducted in sub-Saharan Africa and South Asia. Randomised controlled trials were the most frequently used study design. The evidence is concentrated in two types of PMM strategies: implementation strategies (in-service training, continuing education, supervision) and performance-based financing. Major gaps exist in accountability arrangements particularly the use of audit and feedback. The least studied types of outcomes were unintended effects, harm and social equity. Conclusions: The evidence is clustered around interventions that are unlikely to achieve transformational change in health outcomes. The gaps identified suggest that routinely used PMM strategies are implemented without sufficient knowledge of their effects. Future efforts at redesigning PHC systems need to be informed by evidence on the most effective approaches for using PMM strategies.